A Static Layout Algorithm for DiaMeta - Maier, Sonja; Minas, Mark (Electronic Communications of the EASST, 2008)
The diagram editor generator framework DiaMeta utilizes meta-model-based language specifications and supports free-hand as well as structured editing. In this paper we present a layouting approach that is especially well suited for a static layout. It is based on the layout algorithm presented in a previous paper that uses the two concepts constraint satisfaction and attribute evaluation. This algorithm is combined with graph transformations and the result is a natural way of describing the layout of visual languages. As an example we use a simplified version of Sugiyama's algorithm, applied to statechart diagrams.